SYSTOLIC BLOOD PRESSURE AT BIRTH: THE IMPACT OF MOTHER[Combining Acute Accent]S OBESITY. (April 2021) - Alvarez, Julio; Torro, Maria Isabel; Redon, Pau; Aguilar, Francisco; Redon, Josep; Lurbe, Empar
Abstract : Objective: Rates of overweight and obesity are high in the obstetric population, and this is of particular importance because being overweight prior to pregnancy increases, among others, the risk for infants being large for gestational age. The impact of mother[Combining Acute Accent]s weight condition on BP at birth has not been previously analyzed. Design and method: Three hundred and twenty one newborns (160 females) born at term (gestational age > 36 weeks) after uncomplicated pregnancies and in the absence of perinatal illness were included. Subjects were divided according to size at birth in small, appropriate, and large for gestational age. Anthropometric parameters were obtained at birth and BP was measured on the second day of life. Mother[Combining Acute Accent]s characteristics were obtained. Results: Among mother's characteristics were: age (mean age 32.0 ± 4.6 years), smoking habits (no smokers 70.7%, heavy smokers 4.6%) weight gain during pregnancy (mean 12.8 ± 5.9 kg) and normal weight, overweight and obese (32.4%, 28%, 39.6% respectively). Subjects according to size at birth were small, appropriate, and large for gestational age, 6.9%, 74.5% and 18.6%, respectively. Mother[Combining Acute Accent]s weight was positively related with birth weight (r = 0.212, p < 0.001), length (r = 0.132, p = 0.03) and head circumference (r = 0.194, p = 0.01). Likewise, a positive relationship between SBP and birth weight (r = 0.43, p < 0.001), and SBP with mother[Combining Acute Accent]s weight (r 0.22, <0.001), were observed. When gestational age, sex, length, head circumference and mother[Combining Acute Accent]s characteristics were considered, birth weight was the main and positive determinant of SBP at birth. In addition, mother[Combining Acute Accent]s weight condition assessed by BMI (kg/m2) was also an independent determinant. The concurrent influence of both birth weight and mothers[Combining Acute Accent] BMI is shown in the table. Figure. No caption available. Conclusions: Systolic BP at birth depends of birth weight and mother[Combining Acute Accent]s weight categories. The increment on the prevalence of obesity before pregnancy may contribute to future BP elevation in the offspring.